Study of lattice dynamics of silicon - Thapa, SRB (BIBECHANA, 2012)
Lattice dynamics of Si has been investigated by using a Urey-Bradley Valence Force Field (UVFF) model which is a phenomenological model. In this model following interactions are taken into account: (i) the central force due to bond-stretching (ii) the angular force due to bond bending (iii) central force between non-bonded atoms (iv) the force due to interaction of one internal co-ordinate to adjacent internal coordinate. Calculated results of phonon dispersion curves, Debye Characteristic temperature, microscopic elastic constants and Bulk modulus of Si are compared with experimental results giving fairly good agreement. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7145 BIBECHANA 9 (2013) 13-17